2003
DOI: 10.1002/eji.200323381
|View full text |Cite
|
Sign up to set email alerts
|

CD55/decay accelerating factor is part of the lipopolysaccharide‐induced receptor complex

Abstract: Recently, we described an 80-kDa lipopolysaccharide (LPS)-binding membrane protein to be identical to CD55 [decay accelerating factor (DAF)]. Here, we demonstrate that CD55 is able to contribute to lipopolysaccharide (LPS) signaling. Transfection of Chinese hamster ovary (CHO) cells with human CD55 resulted in a translocation of NF-‹ B after stimulation with LPS as well as with free lipid A. In addition, interaction of lipid A and CD55 was shown by co-immuno-precipitation of these molecules from CHO-CD55 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…Therefore, the effect of LPS on the adipocyte cannot be directly related to the presence of CD14 on its membrane. However, it is possible that this effect occurs via the secretion of CD14 by the adipose cell (Su et al 1999), or possibly as a result of another receptor (Frleta et al 2003;Heine et al 2003). The expression of CD55 on the mature adipocyte would seem to agree with this hypothesis.…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, the effect of LPS on the adipocyte cannot be directly related to the presence of CD14 on its membrane. However, it is possible that this effect occurs via the secretion of CD14 by the adipose cell (Su et al 1999), or possibly as a result of another receptor (Frleta et al 2003;Heine et al 2003). The expression of CD55 on the mature adipocyte would seem to agree with this hypothesis.…”
Section: Discussionmentioning
confidence: 61%
“…Signaling proteins at the cell surface, TLR4 and MD-2, which are involved in the perception of the stimulus, connect to several intracellular signaling cascades orchestrating the process of the cellular response. Recent investigations have revealed that the receptor complex is not a static structure but assembles upon stimulation with LPS by movement of the proteins into lipid raft domains of the cytoplasmic membrane, resulting in the formation of an active signaling complex (21)(22)(23). However, the molecular mechanisms of this receptor recruitment to specific membrane domains are not understood.…”
Section: Discussionmentioning
confidence: 99%
“…Only TLR2 has been shown to associate with other TLRs to build heteromeric receptors (10). TLR4/MD-2 as been found to associate in complexes that include CD11/CD18, CD55, CD81, hsp70, hsp90, GDF5, and CXCR4 (21)(22)(23). However, for most of these proteins, a functional participation in signal transduction is not clear, yet.…”
mentioning
confidence: 99%
“…The possibility that additional receptor components such as integrins, 11,12 heat-shock proteins, 13,14 CXCR4, 14 or CD55 15 have been suggested to be part of this activation cluster, possibly acting as additional LPS transfer molecules. The involvement of K + channels in LPS signal transduction have also been suggested.…”
Section: Lps Recognitionmentioning
confidence: 97%